Pengaruh Media Youtube Belajar Prestasi Pada Pembelajaran Teks Negosiasi Siswa Kelas X Smkn 1 Klari - Permatasari, Destiya Ayu; Syafroni, Roni Nugraha; Rosalina, Sinta (Peneliti.net, 2024)
This research is motivated by the facts that occur in the field, namely students are lazy and bored in learning. In addition, there are still many teachers who use conventional learning models, namely lectures without using media in teaching aids. Thus, researchers want to compare the use of Youtube media in learning and not using Youtube media in learning. This study aims to examine differences in improving student learning outcomes in learning negotiating text using YouTube media in learning and by not using Youtube media in learning. To answer the problem formulation, the researcher used a quasi-experimental non-equivalent pre-test post-test control group design method. The population in this study was class X SMKN 1 Klari with purposive sampling and two classes were selected, namely class X MP-1 (N=40) as the experimental class using Youtube media and class X TKJ-1 (N=40) as the experimental class. control using Youtube media. Based on the results of data processing using SPSS 16 Software for Windows, it was concluded that the average pre-test score for the two classes was relatively the same before being given treatment, namely 56 for the experimental class and 55 for the control class. Then the post-test score for the experimental class was 86 and the control class was 67. Furthermore, the N-gain score for the experimental class was 0.681, which means that there was a change before and after using Youtube media with moderate interpretation in learning negotiating text for class X students of SMKN 1 Klari. Whereas for the control class the N-Gain score showed a result of 0.681, which means that there were changes before and after using the lecture model without Youtube with low interpretation in learning negotiating text for class X students of SMKN 1 Klari. This means that the use of Youtube media is better than the lecture learning model without Youtube and there are significant differences in the learning outcomes of class X students at SMKN 1 Klari.